A pathway-centric survey of somatic mutations in Chinese patients with colorectal carcinomas. - Chao Ling; Lin Wang; Zheng Wang; Luming Xu; Lifang Sun; Hui Yang; Wei-Dong Li; Kai Wang (PLoS ONE, 2015)
Previous genetic studies on colorectal carcinomas (CRC) have identified multiple somatic mutations in four candidate pathways (TGF-β, Wnt, P53 and RTK-RAS pathways) on populations of European ancestry. However, it is under-studied whether other populations harbor different sets of hot-spot somatic mutations in these pathways and other oncogenes. In this study, to evaluate the mutational spectrum of novel somatic mutations, we assessed 41 pairs of tumor-stroma tissues from Chinese patients with CRC, including 29 colon carcinomas and 12 rectal carcinomas. We designed Illumina Custom Amplicon panel to target 43 genes, including genes in the four candidate pathways, as well as several known oncogenes for other cancers. Candidate mutations were validated by Sanger sequencing, and we further used SIFT and PolyPhen-2 to assess potentially functional mutations. We discovered 3 new somatic mutations in gene APC, TCF7L2, and PIK3CA that had never been reported in the COSMIC or NCI-60 databases. Additionally, we confirmed 6 known somatic mutations in gene SMAD4, APC, FBXW7, BRAF and PTEN in Chinese CRC patients. While most were previously reported in CRC, one mutation in PTEN was reported only in malignant endometrium cancer. Our study confirmed the existence of known somatic mutations in the four candidate pathways for CRC in Chinese patients. We also discovered a number of novel somatic mutations in these pathways, which may have implications for the pathogenesis of CRC.